Drying of soybean seeds in a radial air flow dryer. I. Physical monitoring - Sales, Luiz Carlos de Oliveira; Silva, Walter Rodrigues da; Cavariani, Cláudia (Pesquisa Agropecuaria Brasileira, 1999)
The purpose of this research was to study several physical parameters of soybean seed drying submitted to stationary process with radial air distribution by combining different air flows (26.9, 28.4 and 33.2 m3/minute/ton) and temperatures (42, 46 and 50oC), considering seed positions in the seed mass (17, 34 and 51 cm in relation to the insuflation cylinder) and drying periods (zero to twelve hours with two-hour intervals). Environmental air, insuflation air, seed temperatures, moisture content of seeds, drying speed and drying curves were characterized. Considering the evaluated parameters during the drying process, the physical advantages of the combination of 28.4 m3/minute/ton with 46oC, and the desadvantage of the combination of 26.9 m3/minute/ton with 42oC were observed.